Hubungan Dukungan Keluarga dan Kondisi Psikologis Ibu Dengan Tingkat Keberhasilan Pemberian ASI Eksklusif di Desa Paya Geli - Sinaga, Onike Lavionika; Irfani, Putri; Wahyudi, Putri Salsabilla; Hasibuan, Rabiatul Adawiyah; Siregar , Debi Novita (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Breast milk (ASI) is the ideal source of nutrition, containing antibodies and bioactive substances that support infant growth, development, and immune function. Despite its substantial benefits, many mothers fail to exclusively breastfeed. Family support and maternal psychological conditions are strongly suspected to influence the success of exclusive breastfeeding. Objective: This study aims to analyze the relationship between family support and maternal psychological conditions with the success of exclusive breastfeeding in Paya Geli Village. Methods: This quantitative study employed a cross-sectional design involving 32 mothers with infants aged 0–6 months. Data were collected using questionnaires and analyzed through univariate and bivariate analyses with Chi-Square and Fisher’s Exact tests. Results: Analysis of this limited sample showed a statistically significant association between family support (OR = 106.8; 95% CI: 10.0–1149.0; p < 0.001) and maternal psychological conditions (OR = 53.3; 95% CI: 2.7–1046.6; p = 0.0003) with exclusive breastfeeding success. However, the wide confidence intervals (CIs) indicate considerable uncertainty in the estimates. Conclusion: Family support and maternal psychological conditions are critical determinants of exclusive breastfeeding success. Community-level health promotion programs should prioritize these factors to improve exclusive breastfeeding coverage. Policy implications warrant further investigation with larger and more representative samples.